2021
DOI: 10.18632/oncotarget.27881
|View full text |Cite
|
Sign up to set email alerts
|

The interaction between cancer associated fibroblasts and tumor associated macrophages via the osteopontin pathway in the tumor microenvironment of hepatocellular carcinoma

Abstract: Background: Cancer-tumor associated macrophage (TAM)-cancer associated fibroblast (CAF) interactions are an important factor in the tumor microenvironment of hepatocellular carcinoma. Materials and Methods: Hepatic stellate cells (HSCs) were cultured with cancer cell-conditioned medium (Ca.-CM), TAM-CM and CAF-CM, and the expression of CAF markers were evaluated by RT-PCR. Whether HSCs cultured with Ca.-CM, TAM-CM and CAF-CM contributed to the enhanced malignancy of cancer cells was examined using proliferatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(24 citation statements)
references
References 52 publications
(46 reference statements)
0
24
0
Order By: Relevance
“…Macrophage derived factors may promote the activation of resident hepatic stellate cells into myofibroblasts, resulting in a fibrotic environment in liver metastases of pancreatic ductal adenocarcinoma (245). Recently, Tokuda et al showed the significance of osteopontin mediated cancer-TAM-CAF interactions in hepatocellular carcinoma (246).…”
Section: Reciprocal Interactionsmentioning
confidence: 99%
“…Macrophage derived factors may promote the activation of resident hepatic stellate cells into myofibroblasts, resulting in a fibrotic environment in liver metastases of pancreatic ductal adenocarcinoma (245). Recently, Tokuda et al showed the significance of osteopontin mediated cancer-TAM-CAF interactions in hepatocellular carcinoma (246).…”
Section: Reciprocal Interactionsmentioning
confidence: 99%
“…Tokuda et al. have shown that osteopontin is a key molecule involved in cancer-CAF-TAM interactions and that increased osteopontin can promote malignant tumors ( 141 ). This characterizes the importance of cancer cell-TAM-CAF interactions in HCC.…”
Section: The Pro-tumorigenic Effect Of the Relationship Between Strom...mentioning
confidence: 99%
“…The TAM-secreted OPN promotes the secretion of OPN from CAF and leads to increased cancer cell malignancy through upregulation of proliferation, ECM degradation, and migration. Thus, OPN could be a potential new therapeutic target to inhibit cancer-CAF-TAM interactions in HCC (132).…”
Section: The Caf-tam Collaborationmentioning
confidence: 99%